How sedentary and physically active are breast cancer survivors, and which population subgroups have higher or lower levels of these behaviors? - Boyle, Terry; Vallance, J.; Ransom, E.; Lynch, B. (Springer, 2016)
Purpose: Physical activity (PA) and sedentary behavior may influence the physical and mental health of breast cancer survivors; however, few studies have objectively measured these behaviors in this population. We used accelerometers to measure the PA and sedentary time levels of breast cancer survivors and examined the demographic, behavioral, and medical correlates of these behaviors using two complementary approaches. Methods: A total of 259 breast cancer survivors wore an accelerometer for 7 days during waking hours and completed a questionnaire. We used linear regression and classification trees to investigate correlates of PA and sedentary time. Results: The breast cancer survivors in this study (mean age = 61 years, mean time since diagnosis = 3 years) were sedentary for a daily average of 8.2 h, in light-intensity PA for 5.8 h and in moderate-to-vigorous intensity PA (MVPA) for 32 min, with 16 % meeting PA guidelines. Participants with high comorbidity were the least likely to be meeting guidelines (0 %), while a subgroup of participants with no/low comorbidity, a university degree, and higher levels of pre-diagnosis MVPA were the most likely to be meeting guidelines (47 %). Older participants (70+ years) were the most likely to have sedentary time levels at least twice as high as activity levels, while participants who were younger than 70 years and not in the lowest category of pre-diagnosis MVPA were the least likely. Conclusions: Interventions to facilitate physical activity and reduce sedentary time among breast cancer survivors should consider comorbidity status and previous PA experience.